Shear strength parameters of granitic and sedimentary residual soils from the Northern and the Peninsular Malaysia. Issue 1 (November 2021) - Jamaluddin, D; Nujid, M M; Ahmad, A; Sadikon, S F; Ahmad, F
Abstract: Reduction of shear strength and negative suction as the soil in a stable slope becomes saturated during prolonged rainy seasons are the two main causes for a stable slope to fail. A total of 148 and 112 effective shear strength parameters were collected from granitic residual soil and sedimentary residual soil respectively at both the stable slopes and slope failures in the Northern Malaysia. Meanwhile a total of 103 and 65 effective shear strength parameters secondary data were also collected from granitic residual soil and sedimentary residual soil respectively in Peninsular Malaysia including Singapore. Because of the natural variability of residual soil as the results of inconsistent weathering process during residual soil formations, the highly variable values of the shear strength parameters were obtained. The objectives of the research are to determine the best fit distributions for the effective shear strength parameters as well as their mean values for the granitic and sedimentary residual soils both in the Northern and the Peninsular Malaysia. It was found that the normal distributions were the best fit distributions for the transformed data of the effective shear strength parameters for granitic and sedimentary residual soils at both locations. It was also found that, the mean values of effective shear strength parameters in granitic and sedimentary residual soils at both locations were almost the same although a slightly lower value for effective cohesion was obtained for sedimentary residual soil in the Northern Malaysia.